(untitled) (mathematica didactica, 2021)
Bayesian reasoning problems are a field for misconceptions. Visualizations are assumed to support students when dealing with such problems. Which visualisations (tree diagram or unit square) and information format (probabilities or natural frequencies) support learning, is subject matter of current research. This contribution approaches this question by presenting preferences of visualisations and conceptual knowledge of learners of a 10th-class after a lesson sequence. The results of the survey indicate that students prefer tree diagrams with natural frequencies rather than unit squares. More-over, many students are able to interpret a unit square. Implications of this explorative study for mathematics education are discussed.